(untitled) (Research, Society and Development, 2020)
Objective: to analyze how adolescents perceive the process of identifying/defining the orientation of sexual desire. Methodology: a qualitative study using focus groups with high school students from public and private schools. Five focus groups were carried out, totaling 59 students, from 13 to 18 years old, being 37 females and 22 males. The meetings were recorded and transcribed and the data submitted to a comprehensive analysis with the aid of the WebQDA software. Results: the data were classified into two categories of identification/definition of sexual orientation: one resulting from influences from family, society, media and religion; and another established by nature and experimentation. In the first, there is the recognition of gender constraints from an early age and the heteronormative oppression of society. In the second category, the understanding prevailed that sexual attraction arises with puberty and, in the predominant view of girls, there is a need to test to be sure of the orientation of desire, which can change at any time of life, demonstrating greater fluidity of identity sexual activity in females. Conclusion: the process of identification and definition of sexual orientation is marked by heteronormativity that demonstrates constraining the possibilities of expressing sexuality.